Facilitating Spreadsheet Manipulation on Mobile Devices Leveraging Speech - Srinivasan, Arjun; Lee, Bongshin; Stasko, John (Proceedings of the 2018 ACM CHI Workshop on Data Visualization on Mobile Devices, 2018)
Due to the prevalent use of spreadsheet applications, their user interface on a desktop has evolved significantly over time. However, user interfaces for spreadsheet applications on mobile devices are still in a nascent stage and are typically “ported” versions of their desktop counterparts. In this article, we present a simple tabular data manipulation scenario on mobile devices, leveraging speech input. We describe ways to complement direct manipulation-based input via touch or pen with minimalistic speech-based input. We also briefly discuss an open area for future research, where we could explore the role of speech input for interacting with spreadsheets along the spectrum of command-like utterances to a conversational dialog.